Assessing Enamel Thickness to Estimate Interproximal Reduction: A CBCT‐Based Study - Enrique González‐García; Nasib Balut‐Chahin; Claudia Daniela Rojo‐Arce; María Eugenia Jiménez Corona; Luis Pablo Cruz‐Hervert; Jean Marc Retrouvey (Clinical and Experimental Dental Research)
ABSTRACT Objectives The aims of this study were to (1) estimate the mesial and distal proximal enamel thickness available (PETa), (2) estimate the proximal enamel thickness remaining (PETr) on the basis of planned IPR, and (3) assess PETr‐associated risks with varying IPR amounts. Materials and Methods A cross‐sectional study was conducted using CBCT scans. PETa was estimated using on‐demand software. Mesial and distal PET were measured at the middle third of the crown. The means and 95% confidence intervals (CIs) of the PETa and PETr data are reported. Differences between the mesial and distal PETa values were compared. Results A total of 1615 teeth were analyzed via CBCT. The mean PETa values ranged from 0.96 to 1.29 mm (mesial) and from 0.98 to 1.25 mm (distal). Differences between mesial and distal PETa were statistically significant, averaging 0.10 mm proximally (p < 0.050). In particular, these differences were observed in cuspids, including tooth 13 (1.18 ± 0.24 vs. 1.25 ± 0.28; p = 0.021), tooth 23 (1.25 ± 0.26 vs. 1.15 ± 0.28; p < 0.001), tooth 33 (1.22 ± 0.26 vs. 1.10 ± 0.23; p < 0.001), and tooth 43 (1.29 ± 0.24 vs. 1.13 ± 0.20; p < 0.001). The mean PETr values for single‐site IPRs < 0.4 mm were 0.58 mm (mesial) and 0.57 mm (distal). Exceeding a single‐site IPR of 0.20 mm significantly increased the proportion of interproximal sites classified as moderate or high risk, particularly in teeth with thinner enamel (< 0.7 mm). Conclusions PETa and PETr are critical for determining safe and individualized IPR. CBCT‐based PETa evaluations are strongly recommended when single‐site IPRs exceeding 0.20 mm are planned to increase precision and reduce the risk of excessive enamel reduction.